ANALYSIS OF SCIENTIFIC MODELS TO THE PROBLEM OF APPLICATIONS THROUGH EPISTEMOLOGICAL PRINCIPLES IN PSYCHOLOGY - Babajanyan, I. H. (Modern Psychology, 2020)
The article will identify the key points of the epistemological principles in psychology as well as will educate about the approaches and their usefulness well as some background information related to the models that have been previously studied in the field of Psychology. The models aim to focus on the knowledge and the comparison between justified belief and opinion. Moreover, they also try to educate the aspects of cognitive processing’s which may include the argumentative processes, how one perceives the world experiences through epistemological assumptions. Current trends in psychological research are explained in the article through epistemological principles. In addition to the descriptions of each psychological study, which used epistemological methods to study the thought processes of various populated samples, a comparative analysis is also provided.